Time Trial positioning in elite cyclists - exploring the physiological effects of adapting to a lower torso position - Cubel, C.; Feder Piil, J.; Nybo, L. (Journal of Science and Cycling, 2022)
Lowering of the upper body to optimize cycling time trial (TT) performance is a balance between the aerodynamic advantage related to a lower frontal area and prospective detrimental physiological effects associated with a reduction of the hip-torso angle. To explore this in elite athletes and across positions relevant for competitive cyclists, we analysed racing positions for world championships [WC] top-10 finishers and 10 national elite TT-cyclists. Subsequently, laboratory studies were completed to evaluate effects on exercise economy, muscle oxygenation and perceived exertion for the national TT-group for their habitual position and compared to standard (4-12-20°) torso angles. Hence, covering the racing position observed for top-10 WC finishers (positioned from 4-12°) and the national elite (range 8-18°). Oxygen calorimetry and near-infrared spectroscopy revealed that there was no difference in overall energy expenditure, delta exercise efficiency or muscle oxygenation across the investigated range of positions. However, rating of perceived exertion was significantly elevated for the lowest position (4° torso angle) compared to the rider`s habitual position. This lets us conclude that elite TT-cyclists can acutely adopt to a very low upper body position without compromising exercise economy or muscle oxygenation and some WC-level TT riders have adopted this low (4°) racing position. However, the elevated perception of exertion with an acute reduction of the torso-hip angle indicates that it presumably requires specific training in the position or factors not related to exercise economy and muscle oxygenation determine if a rider in practice can perform in the very low position.